Replacing Dopamine Neurons in Parkinson’s Disease: How did it happen? - Björklund, Anders (J Parkinsons Dis, 2017)
The efforts to develop a dopamine cell replacement therapy for Parkinson’s disease have spanned over more than three decades. Based on almost 10 years of transplantation studies in animal models, the first patients receiving grafts of fetal-derived dopamine neuroblasts were operated in Lund in 1987. Over the following two decades, a total of 18 patients were transplanted and followed closely by our team with mixed but also very encouraging results. In this article we tell the story of how the preclinical and clinical transplantation program in Lund evolved. We recall the excitement when we obtained the first evidence for survival and function of transplanted neurons in the diseased human brain. We also remember the setbacks that we have experienced during these 30 years and discuss the very interesting developments that are now taking place in this exciting field.